1993
DOI: 10.1007/bf02247364
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam and gepirone selectively attenuate either 20–32 or 32–64 kHz ultrasonic vocalizations during aggressive encounters

Abstract: Ultrasonic vocalizations (USV) in rats may communicate "affective" states, as they occur only in highly significant behavioral contexts such as during sex, aggression, exposure to painful or startling events. This proposal was evaluated in an experiment with adult male Long-Evans rats during agonistic encounters; specifically, the effects of diazepam, flumazenil and gepirone were studied on different types of USV emitted by intruder rats exposed to resident attacks and to "threat of attacks" (i.e., intruder pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 39 publications
2
39
1
Order By: Relevance
“…CLM 20 mg/kg (n=6) or vehicle (n=6) was injected intraperitoneally 45 min before each session. The doses of DZP and CLM were selected according to the previous reports in which these drugs showed decreasing effects on the USVs in rats [9,38] Data analysis: Data analyses were performed with StatView + Graphics 4.1J (Abacus Concepts, Inc., Berkeley, CA, U.S.A.). The significance level for all statistical tests was set at p=0.05.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLM 20 mg/kg (n=6) or vehicle (n=6) was injected intraperitoneally 45 min before each session. The doses of DZP and CLM were selected according to the previous reports in which these drugs showed decreasing effects on the USVs in rats [9,38] Data analysis: Data analyses were performed with StatView + Graphics 4.1J (Abacus Concepts, Inc., Berkeley, CA, U.S.A.). The significance level for all statistical tests was set at p=0.05.…”
Section: Animalsmentioning
confidence: 99%
“…Behavioral modification is, however, sometimes accompanied by an increase in anxiety or aggression [20]. Supplementary drug treatment is also efficacious against behavioral symptoms in dogs [18], although the interaction between behavioral modification and drug treatment has not been well established.Rodents emit ultrasonic vocalizations (USVs) under adverse circumstances, such as being separated from littermates [1,24], during agonistic confrontations [22,30,35,38], and being exposed to foot shocks [9,36] or to acoustic stimuli [16]. It has been demonstrated that the USVs induced by foot shocks are mediated by corticotropinereleasing factor [17] and are attenuated by anti-anxiety drugs in adult rats [9,36], and thus the USVs have been regarded as a good index for anxiety status in this animal model [9,22].…”
mentioning
confidence: 99%
“…The results show clear differences between rats experiencing complex and novel housing also been demonstrated to denote good welfare in laboratory rats (Manser, 1992;Blanchard et al, 1995;Haller et al, 1998;Tsai et al, 2003;Živkovic et al, 2005). Similarly, aggression, non-aggressive social interaction, awake non-active behaviours, away from enrichment, underneath hopper and audible vocalizations have been used to judge the welfare of laboratory rodents with elevated levels being indicative of a generally compromised welfare state (Adams, 1977;Vivian and Miczek, 1993;Marashi et al, 2004; see also Fureix and Meagher 2016). One reason why non-aggressive social interaction may be related to poor welfare is that it may induce aggressive responses in laboratory rodents by increasing the chance that two rats in a cage meet or come in to direct contact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the production of audible vocalizations (within the human hearing range) appears to be linked to stressful situations such as attack encounters and defensive behaviours (Blanchard et al, 1986;Kaltwasser, 1990;Vivian and Miczek, 1993), to pain such as electric tail shock (Van Der Poel and Miczek, 1991) and to handling (Adams, 1977), and may therefore reflect a negative welfare state in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, signs that oscillate from irritability to extreme fear behaviours and seizures have already been described (Ashton, 2005;Emmett-Oglesby et al, 1983a;Lacerra et al, 1999;Owen and Tyrer, 1983;Lader, 1981a, 1981b;Woods et al, 1987). For example, rats withdrawn from diazepam exhibited high levels of aversion when submitted to the elevated plus-maze (EPM) (File and Andrews, 1991;Martijena et al, 1996), increased levels of ultrasonic vocalizations (USV) on 22-KHz frequencies and enhanced startle response amplitude to an auditory startling-eliciting stimulus (Vivian et al, 1994;Vivian and Miczek, 1993). A similar level of defensive behaviour is observed in animals faced with several dangerous situations such as exposure to predators (Blanchard et al, 1991), foot-shocks (De Vry et al, 1993) or playback of 22-KHz aversive frequencies (Brudzynski and Chiu, 1995).…”
Section: Introductionmentioning
confidence: 99%